Slang Words Used by Teenagers in their Daily Life while Texting with their Friends - Isabela Aileen (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This was a descriptive qualitative study of slang words used by teenagers in their daily life while texting with their friends. In order to find the most used slang words and the most used type of word formation in that slang words the writer’s used one main theory which is theory of word formation processes by Yule (2010) supported by the definition of slang words by Connie Eble (2012). The findings revealed that the kind of slang words that are being used are Indonesian slang words, with a total of 23 slang words found in the text messages. In this study the writer also found that the most used word formation processes for the slang words that are used by teenagers when they text each other are clipping with a total number of 24 words.